2001
DOI: 10.1097/00003246-200107000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Application of fiberoptic sensors for the study of hepatic dysoxia in swine hemorrhagic shock

Abstract: The multiple-parameter sensor offers the unique opportunity to study solid as well as hollow organ dysoxia through the simultaneous measurement of interstitial pH, Pco2, and Po2 in a small tissue region. The gradual transition from sufficient oxygen availability to dysoxia as a result of hemorrhage was better described by an exponential equation. The length of time that pH was below or Pco2 was above the critical value determined from the exponential model was predictive of a negative outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…pHm is significantly decreased at an LBNP level of Ϫ70 mmHg, corresponding to a fall in PmO 2 to 27.4 Ϯ 1.7 mmHg. We previously demonstrated a similar relationship between tissue pH and tissue PO 2 in swine liver during hemorrhagic shock (27). In this animal study, measurements of tissue pH and PO 2 with invasive sensors demonstrated a breakpoint (PO 2 crit) where pH began to decrease after tissue PO 2 had decreased to 22.3 Ϯ 3.8 mmHg (linear model; Ref.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…pHm is significantly decreased at an LBNP level of Ϫ70 mmHg, corresponding to a fall in PmO 2 to 27.4 Ϯ 1.7 mmHg. We previously demonstrated a similar relationship between tissue pH and tissue PO 2 in swine liver during hemorrhagic shock (27). In this animal study, measurements of tissue pH and PO 2 with invasive sensors demonstrated a breakpoint (PO 2 crit) where pH began to decrease after tissue PO 2 had decreased to 22.3 Ϯ 3.8 mmHg (linear model; Ref.…”
Section: Discussionsupporting
confidence: 62%
“…It is also possible to determine muscle pH (pHm) using NIRS (28, 37). In swine hemorrhage, tissue pH is significantly more sensitive to shock than measures of arterial and venous pH (26), and depressed tissue pH is strongly associated with negative outcomes (27). From a practical standpoint, NIRS instruments can be made small and portable, allowing them to be used for rapid, noninvasive patient assessment both inside and outside the hospital.…”
mentioning
confidence: 99%
“…Unfortunately, no data are available on the in vivo oxygen partial pressure in rainbow trout liver tissue. In mammalian liver tissue, oxygen levels detected are in the range of 4-6·kPa, whereas at concentrations of 1.5-1.7·kPa, oxygen availability no longer matches consumption (Soller et al, 2001;Brooks et al, 2004). 'Physiologically normoxic' and 'critical' oxygen tensions correspond with 5-3% and 1% O 2 levels in gas phase, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…In animal models, such prolonged increases in P L CO 2 are associated with hepatocellular damage [11]. The aim of this study was to describe the changes that occur in liver tissue pH, P L CO 2 , and P L O 2 during IPC and to define the optimal IPC regime, using P L CO 2 as a predictor of hepatocellular damage.…”
Section: Introductionmentioning
confidence: 99%